New Research Uncovers Makeup of Mcintyre Powder, Inhaled by Underground Miners for Decades (CBC News, 2019)
Before each shift between the 1940s and 1970s, underground miners in northern Ontario breathed in a substance they thought was protecting their lungs, but none of them knew what exactly was in McIntyre Powder. Until now. –Website description.

Unbreakable: The Spirit of the Strike - University of Manitoba Libraries; City of Winnipeg Archives; University of Winnipeg Archives; University of Calgary Archives and Special Collections; Winnipeg Police Museum (Unbreakable, 2019)
A digital exhibit commemorating the 100th anniversary of the Winnipeg General Strike. The exhibit also provides a listing of archival sources available locally, in Manitoba, and online. Content is drawn from the University of Manitoba Libraries, the City of Winnipeg Archives, the University of Winnipeg Archives, the University of Calgary Archives, and the Winnipeg Police Museum. The primary resources were developed in collaboration with the Association for Manitoba Archives and its members.